The Sensitivity of Southern Ocean Air‐Sea Carbon Fluxes to Background Turbulent Diapycnal Mixing Variability - Ellison, Elizabeth; Mashayek, Ali; Mazloff, Matthew (American Geophysical Union (AGU), 2023)
Funder: UK Engineering and Physical Sciences Research Council Abstract The Southern Ocean (SO) connects major ocean basins and hosts large air‐sea carbon fluxes due to the resurfacing of deep nutrient and carbon‐rich waters. While wind‐induced turbulent mixing in the SO mixed layer is significant for air‐sea fluxes, the importance of the orders‐of‐magnitude weaker background mixing below is less well understood. The direct impact of altering background mixing on tracers, as opposed to the response due to a longer‐term change in large‐scale ocean circulation, is also poorly studied. Topographically induced upward propagating lee waves, wind‐induced downward propagating waves generated at the base of the mixed layer, shoaling of southward propagating internal tides, and turbulence under sea ice are among the processes known to induce upper ocean background turbulence but typically are not represented in models. Here, we show that abruptly altering the background mixing in the SO over a range of values typically used in climate models ( m 2 s −1 – m 2 s −1 ) can lead to a ∼70% change in annual SO air‐sea CO 2 fluxes in the first year of perturbations, and around a ∼40% change in annual SO air‐sea CO 2 fluxes over the 6‐year duration of the experiment, with even greater changes on a seasonal timescale. This is primarily through altering the temperature and the dissolved inorganic carbon and alkalinity ...